Pengaruh Efikasi Diri, Beban Kerja dan Work Life Balance Terhadap Kepuasan Kerja Karyawan Di PT. Telkom Indonesia Witel Solo - Titis Sukma Rosalita; Riska Fii Ahsani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study is a survey study on employees of PT. Telkom Indonesia Witel Solo. The purpose of this study is to examine the effect of self-efficacy, workload and work life balance on job satisfaction. The type of data used is quantitative data, the data source used is primary data. Data collection in this study was carried out by distributing researcher questionnaires to the relevant respondents. The population in this study were employees of PT. Telkom Indonesia Witel Solo. The sampling technique in this study used simple random sampling technique and obtained a sample of 120 respondents. Data were collected with a questionnaire that had been tested for validity and reliability. The data analysis technique used multiple linear regression analysis, t-test, F-test and coefficient of determination (R2).The results of this study indicate that self-efficacy has a significant effect on employee job satisfaction at PT. Telkom Indonesia Witel Solo. Workload has a significant effect on employee job satisfaction at PT. Telkom Indonesia Witel Solo. Work life balance has a significant effect on employee job satisfaction at PT. Telkom Indonesia Witel Solo. The results of the determination coefficient obtained an adjusted R square value of 0.438, which means that the contribution of the influence of the variables self-efficacy, workload and work life balance to the job satisfaction variable is 43.8%